Pengembangan Video Knowledge Capture Mata Kuliah Difusi Inovasi Pendidikan di Prodi Teknologi Pendidikan Universitas Negeri Jakarta - Ardiansyah Ardiansyah; Kunto Imbar Nursetyo; Cecep Kustandi (Jurnal Pembelajaran Inovatif, 2020)
This research aims to produce video of knowledge capture for Educational Innovation Diffusion courses in Educational Technology, Universitas Negeri Jakarta. The development of this video is expected can be learning resources for student of Educational Technology. Development of Knowledge Capture Video uses the Model Video Nonlinear by Pustekkom, this model has 3 major stages and sub stages at each stages. This research involves three trials protester, consist of expert review, one to one, and small group. The development of knowledge capture video involves two expert review (review expert matter and media expert). Formative evaluation conducted by researchers refer to a survey web bali state university of Jakarta and uses a likert scale (1-4). Average result from expert review 3,85, One on one 3,28, and small group 3,42. Based on the result of these data, reseacrcher conclude that video knowledge capture worth to use as a source of learning.